Geochemistry and mineralogy of the Truc Thon Clay, Hai Duong Province, North Vietnam: implication for paleoclimatic and provenance analysis - Hoang Van, Tha; Iqbal, Shahid; Czarniecka, Urszula; Wysocka, Anna; Phan Dong, Pha; Nguyen Quoc, Cuong; Vu Van, Ha; Dang Minh, Tuan (Vietnam Journal of Earth Sciences, 2021)
During the Miocene-Pleistocene, generally sub-tropical to tropical warm and humid paleoclimate prevailed in Southeast Asia with a gradual cooling trend. The Truc Thon clay (TTC) mine presents interesting outcrops for sedimentological and provenance analysis. The present study uses results of geological investigation in 16 outcrops and wells at the clay mine Truc Thon. The TTC has lens-shaped geometry, filled with two clay bodies, including grey-white clay and multicolor clay. Bulk mineralogy indicates the predominance of quartz and a relatively high amount of pyrophyllite. Clay mineralogy shows the presence of main kaolinite, followed by illite and mixed-layer illite-smectite. These may interpret a warm, humid paleoclimatic condition in the source areas. Illite may be inherited from basement rocks. The bulk rock geochemistry supports intense chemical weathering with the Chemical Index of Alteration (CIA) in the TTC ranged ca. 80.6-98 (average = 90.4). In combination with the geochemical proxies and the mineralogical composition of the TTC, the chemical weathering intensity indicated warm/hot, semi-humid/humid tropical paleoclimate in the source area. A combination of mineralogical and geochemical analyses with regional geological features show that the Hon Gai Triassic rocks are the main source for the TTC. Source materials are originally related to silicic rocks of granitic-granodioritic composition. Paleoclimatic conditions favored intense chemical weathering of the Hon Gai Triassic rocks and surrounding rocks, creating a ceramic mine of great industrial value.